Analysis and Design of a Tapped Inductor Boost Converter - Kaweewat Tattiwong; Siripan Trakuldit; Chanin Bunlaksananusorn (My University, 2023)
This paper presents an analysis and design of a Tapped Inductor Boost Converter (TBC). The converter operation is analyzed, resulting in key voltage and current expressions for the circuit. Based on the derived equations, a prototype converter is designed and subsequently used for experiment. It is found that the experimental results are consistent with the analytical values.
Keywords: Advanced DC-DC Converters; Multilevel Inverters and Converters; Silicon Carbide Semiconductor Technologies